2009
DOI: 10.1002/adsc.200800775
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Applications of Laccase in Green Chemistry

Abstract: Laccases (benzenediol:oxygen oxidoreductase, EC 1.10.3.2), multi‐copper‐containing oxidoreductase enzymes, are able to catalyze the oxidation of various low‐molecular weight compounds, specifically, phenols and anilines, while concomitantly reducing molecular oxygen to water. Because of their high stability, selectivity for phenolic substructures, and mild reaction conditions, laccases are attractive for fine chemical synthesis. This review provides a discussion of the recent applications of this interesting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
178
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(181 citation statements)
references
References 162 publications
1
178
0
2
Order By: Relevance
“…1.10.3.2, see Riva, 2006;Rodgers et al, 2010;Witayakran & Ragauskas, 2009), in combination with the mediator TEMPO for laccase regeneration (Bragd, van Bekkum, & Besemer, 2004), oxidizes primary hydroxyl groups of GM in an unbuffered aqueous solution of guar galactomannan, causing a substantial viscosity increase of the polysaccharide solution, which is converted to an elastic gel, as confirmed by its modified rheological profile. In a follow-up publication (Merlini et al, 2015), we reported that the laccase/TEMPO oxidation system yields elastic gels also in the case of four other leguminous gum solutions (i.e., locust bean, tara, sesbania and fenugreek) and have also shown that the higher the galactose content of the GM, the higher the viscosity increase.…”
mentioning
confidence: 99%
“…1.10.3.2, see Riva, 2006;Rodgers et al, 2010;Witayakran & Ragauskas, 2009), in combination with the mediator TEMPO for laccase regeneration (Bragd, van Bekkum, & Besemer, 2004), oxidizes primary hydroxyl groups of GM in an unbuffered aqueous solution of guar galactomannan, causing a substantial viscosity increase of the polysaccharide solution, which is converted to an elastic gel, as confirmed by its modified rheological profile. In a follow-up publication (Merlini et al, 2015), we reported that the laccase/TEMPO oxidation system yields elastic gels also in the case of four other leguminous gum solutions (i.e., locust bean, tara, sesbania and fenugreek) and have also shown that the higher the galactose content of the GM, the higher the viscosity increase.…”
mentioning
confidence: 99%
“…This enzyme has been used to synthesize hydroxybiphenyl dimers 14 , isoeugenol dimers 15 , and ferulic acid dimers 16 . Laccase is also able to couple a laccase substrate with a non-laccase substrate (known as a mediator) to create new molecules (heterodimers) 8,17 . Niedermeyer et al reported the heterodimeric synthesis among p-hydroquinones and primary aromatic amines using laccase 10 .…”
Section: Introductionmentioning
confidence: 99%
“…It is a multi-copper containing oxidoreductase (EC 1.10.3.2) with four copper centers (one type 1, one type 2 and two type 3 Cu atoms), which catalyzes the oxidation of a variety of phenols to quinones through the activation of molecular oxygen. 13 Laccase has been studied in several organic transformations such as the preparation of phenolderivatives, aldehydes, ketones, lactones, oxidations of azo-dyes, hormones, polymerization reactions, and others. 13 In addition to copper-containing laccase, tyrosinase and catechol oxidase have also received special attention related to their use as green catalysts because of their catecholase activity, i.e., their ability to convert 1,2-dihydroxyphenols (o-diphenol or catechol) to the respective o-quinones.…”
Section: Introductionmentioning
confidence: 99%
“…13 Laccase has been studied in several organic transformations such as the preparation of phenolderivatives, aldehydes, ketones, lactones, oxidations of azo-dyes, hormones, polymerization reactions, and others. 13 In addition to copper-containing laccase, tyrosinase and catechol oxidase have also received special attention related to their use as green catalysts because of their catecholase activity, i.e., their ability to convert 1,2-dihydroxyphenols (o-diphenol or catechol) to the respective o-quinones. However, besides this feature, tyrosinase is also able to promote the o-hydroxylation of phenols (cresolase activity) and may contribute to bioremediation of phenol-containing industrial residues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation